VD_FINDINFO HC / 2012 / 680 vom 27. September 2012 - VD Tribunal cantonal (2012)
DEVIS, HONORAIRES, CONTRAT D'ENTREPRISE, APPRÉCIATION DES PREUVES | 8 CC, 29 Cst., 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 405 al. 1 CPC (CH)